THE EFFECT OF WORK DISCIPLINE AND JOB TRAINING ON THE PERFORMANCE OF KARYWAN PT. TAMARIND MEDAN - Dewi, Sumitra; Mujiatun, Siti (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2022)
The problem of  this  study  is,   this study  aims  to  find out  and analyze  work  discipline  and   job training  that affect    employee  performance  at PT.  Tamarind    Medan. Of the several  problems  that exist  in PT.  Asam  Jawa  Medan, the author  limits  the problem  of  Work  Discipline  and   Job Training.  The purpose of  this  study  is  to  determine  the effect of  Work  Discipline  and   Job Training  on the  Performance  of   PT.  Tamarind    Medan.  The research used  in  this  study  is  a   Quantitative  approach.  In  determining  the sample , this  study  used a   saturated  technique  where  all  populations  were sampled. The  data collection technique   used in    this  study  is  a questionnaire  (Questionnaire), to  analyze the   data and information needed , the  author  uses  data   techniques  where    hypothesis  testing  is used after  going through  stages  such as  distributing  questionnaires.  To  test the   quality  of the questionnaire  using the Validity  and Reliability  Test. The analysis  technique used  in  this  study  is  a Quantitative  data   analysis technique, which  uses  the calculation  of numbers  and then  draws  conclusions  from the   test    with Multiple  Linear   Regression,   Classical assumptions, Persial  Test (t), Simultaneous  (f), between  Work discipline    and   Job training  Against Employee  Performance   shows  t count  greater than      ttable  of  such  results  that  Ha is captured  and Ho is rejected.  Based on  the test results    of the value  showing  Fcount  is greater than      Ftable, Ho is rejected  so it   can  be concluded  that  there is  a significant  overwriting  between  disciplines   job and  job training    on  karywan  values. R-Square Value Variable  Y (Employee performance) can  be explained  by   the variables of work  discipline  (X1), Job training    (X2), against  employee  performance  (Y), and the rest  is influenced  by variables  that tidal researched.